How is mhealth and web-based telemedicine implemented in patient with hypertension? : a narrative scoping review - Gautama, Made Satya Nugraha (Holistic Nursing Plus, 2023)
In this digital era, telemedicine has become one of the cutting-edge approaches that is feasible for hypertension management. Despite the proliferation of trial research, reviews of how telemedicine is practiced are limited. The aim of this study is to review how telehealth is applied in patients with hypertension. A scoping review according to the Joanna Briggs Institute Reviewer Manual's instructions was used with a narrative approach to the type of RCT intervention articles. The search was conducted through electronic databases Scopus, PubMed, and Medline-OVID with the keywords "Telemedicine" and "hypertension". Of 1945 articles, 13 studies met the criteria and were reviewed. Telemedicine interventions including mhealth-based and web-based provide various ways to manage and provide telemonitoring for BP. The utilization of m-health can be through the development of smartphone applications, text messaging, or the use of current social media. Whereas web-based utilization mostly uses email consultations and not many uses paid websites but are integrated with mobile phones. Telemedicine whether mhealth or web-based makes it easier for healthcare professionals to manage and monitor patients' BP, offering a sustainable positive impact in the future.